A Minor Innovation in Constructing a Small Bowel Stoma in Neonates with Small Bowel Atresia to Reduce the Morbidity - Naeem Khan; Saba Bakht; Nadia Zaheer (EL-Med-Pub, 2020)
Background: Intestinal atresia has still significant morbidity in developing countries. Stomas are now not recommended in every case of intestinal atresia; primary anastomosis is the goal of surgery after resection of dilated adynamic gut. A new type of stoma formation along with primary anastomosis is being presented here. Materials and Methods: This report is based on our experience of many cases with this technique in last 12 years but all the details and long follow-up of each case is not available. However the method of surgical procedure, progress, complications, and advantages encountered have been highlighted. Results: Presently we have data of 7 patients; others are lost to follow up. Three had died with other associated problems, namely one with multiple atresias, two with septic shock and prematurity. Two stomas did not require formal closure because stoma shriveled and disappeared. Two other stomas had grown very long like a diverticulum when these were closed after 5 and 8 months. Conclusion: This technique is another attempt to decrease morbidity of patients of intestinal atresia especially in those cases where short bowel syndrome is feared after resection of proximal dilated gut.